GUN1-Interacting Proteins Open the Door for Retrograde Signaling. (October 2019) - Jia, Yuebin; Tian, Huiyu; Zhang, Shuo; Ding, Zhaojun; Ma, Changle
Abstract : Genomes Uncoupled 1 (GUN1) plays a critical role in various retrograde signaling pathways. Despite numerous studies, the precise molecular mechanism underlying GUN1-mediated retrograde signaling remains elusive. Recently, MORF2 and cpHSC70 have been identified as GUN1-interacting proteins, linking retrograde signaling with plastid RNA editing and cytosolic folding stress, respectively.